CANEUS2006: MNT for Aerospace Applications 2006
DOI: 10.1115/caneus2006-11042
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature (800°C) MEMS Pressure Sensor Development Including Reusable Packaging for Rocket Engine Applications

Abstract: For aircraft and rocket engines there is a strong need to measure the pressure in the propulsion system at high temperature (HT) with a high local resolution. Miniaturized sensor elements commercially available show decisive disadvantages. With piezoelectric-based sensors working clearly above 500°C static pressures can not be measured. Optical sensors are very expensive and require complex electronics. SiC sensor prototypes are operated up to 650°C, but require high technological efforts. The present approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Another sensing technology uses Bragg gratings, which are photoinscribed into fibers and used to trace wavelength shifts caused by pressure and temperature changes at temperatures exceeding 350 • C and potentially over 1500 • C [3]. Piezoresistive pressure sensors with diaphragms made from silicon carbide [4], and more recently even Si [5], have been reported to operate at 600 • C. Sapphire membranes have also been used in this context [6].…”
Section: Discharge-based Pressure Sensors Formentioning
confidence: 99%
“…Another sensing technology uses Bragg gratings, which are photoinscribed into fibers and used to trace wavelength shifts caused by pressure and temperature changes at temperatures exceeding 350 • C and potentially over 1500 • C [3]. Piezoresistive pressure sensors with diaphragms made from silicon carbide [4], and more recently even Si [5], have been reported to operate at 600 • C. Sapphire membranes have also been used in this context [6].…”
Section: Discharge-based Pressure Sensors Formentioning
confidence: 99%
“…Piezoresisitve pressure sensors with diaphragms made from silicon carbide [5], and more recently even Si [6], have been reported that can also operate at elevated temperatures. Sapphire membranes have also been used in this context [7].…”
Section: Introductionmentioning
confidence: 99%
“…Bragg gratings have been photo inscribed into fibers and used to trace wavelength shifts caused by pressure changes at temperatures exceeding 350˚C, with the potential of operating at temperatures over 1,500˚C [2]. High temperature piezoresisitve pressure sensors in silicon carbide [3], and more recently even in Si [4], are capable of operating at 600ºC; sensors operating at 800ºC using sapphire membranes have also been developed [5].…”
Section: Introductionmentioning
confidence: 99%